FRI0128 Utility of Enthesitis Assessments in Peripheral Spondyloarthritis – Data from the Ability-2 Trial. (10th June 2014) - Mease, P.; Van den Bosch, F.; Baeten, D.L.; Sieper, J.; Song, I.-H.; Karunaratne, P.M.; Pangan, A.L.
Abstract : Background: Peripheral spondyloarthritis (pSpA) is characterized by arthritis, enthesitis, and/or dactylitis. Enthesitis is considered a core outcome domain for SpA. Clinical assessment of enthesitis is challenging and there is no recommendation for using a specific enthesitis tool in axial or peripheral SpA. 1 ABILITY-2 offers the opportunity to evaluate the use of various enthesitis tools during adalimumab (ADA) treatment of non-psoriatic pSpA. Objectives: To evaluate the 2-year (yr) efficacy of ADA on enthesitis and compare different enthesitis patterns and tools in pSpA Methods: ABILITY-2 is an ongoing, multicenter phase 3 study. Eligible patients (pts) were age ≥18 yrs, fulfilled ASAS peripheral SpA criteria, and had active disease. Pts were randomized to ADA 40 mg every other week (wk) or PBO for 12 wks followed by a 144-wk open-label extension. 29 enthesitis sites based on Leeds, SPARCC and MASES scores were assessed through wk 104. Remission was defined as score =0 during follow-up among pts having baseline (BL) score >0 for enthesitis scores. Results: 165 pts (ADA 84/PBO 81) were randomized. At BL 143 (87%) had ≥1 enthesitis site. Out of those with at least one positive enthesitis site at BL, Leeds was positive in 72.0%, SPARCC in 90.2% and MASES was positive in 86.0%. Mean BL scores for pts receiving ADA vs. PBO were 2.4 vs. 2.3 for Leeds, 5.0 vs. 5.1 for SPARCC and 4.5 vs. 4.5 for MASES. Question 4 of the BASDAI which has previously been regarded as a patient-reported outcome for the presence of enthesitis showed mean values (± standard deviation) of 6.2 (±2.3) in pts with ≥1 enthesitis at baseline (n=143) vs. 5.3 (±2.3) for those without enthesitis at BL (n=22) and thus was not able to discriminate between the 2 pt groups at BL. The Leeds score did better than SPARCC or MASES to discriminate ADA-treated pts from PBO-treated pts at wk 12 (Table). Conclusions: In ABILITY -2, the LEEDS and SPARCC enthesitis tools had better ability compared to the MASES to discriminate the treatment effect of adalimumab on enthesitis in pSpA patients. References: van der Heijde D et al. J Rheumatol 1999;26(4):1003-5. Acknowledgements: AbbVie funded the study (NCT01064856 ), contributed to its design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. Statistical support was provided by Ying Zhang, PhD, of AbbVie. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: P. Mease Grant/research support: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Consultant for: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, F. Van den Bosch Grant/research support: AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer, and UCB, D. Baeten Grant/research support: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, Consultant for: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, J. Sieper Grant/research support: AbbVie, Merck, Pfizer, and UCB, Consultant for: AbbVie, Merck, Pfizer, and UCB, Speakers bureau: AbbVie, Merck, Pfizer, and UCB, I.-H. Song Shareholder of: AbbVie, Employee of: AbbVie, P. Karunaratne Shareholder of: AbbVie, Employee of: AbbVie, A. Pangan Shareholder of: AbbVie, Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.1525